2011
DOI: 10.1111/j.1365-2850.2011.01744.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses attitudes towards the importance of families in psychiatric care following an educational and training intervention program

Abstract: This study measures the attitudes of the psychiatric nurses, after having received an education and training intervention program (ETI-PROGRAM) in family systems nursing, towards the importance of the families in their care. Nurses' knowledge of the impact that family nursing intervention can have on family members may increase positive attitudes towards families. However, little is known about the impact that education and training intervention can have on nurses' attitudes, towards families in clinical pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

23
94
3
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(124 citation statements)
references
References 20 publications
(47 reference statements)
23
94
3
4
Order By: Relevance
“…Among different variables related to scores, in the subscale Family: resources in nursing care, the lowest scores presented in this study were found among nurses who did not have any type of training or contact with contents related to Family Nursing. Similar results were found in studies carried out in contexts of primary health care (16) and psychiatric care (17) , which also included lower academic degrees, that is, undergraduate. Higher scores were also found after online training in interacting with families.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Among different variables related to scores, in the subscale Family: resources in nursing care, the lowest scores presented in this study were found among nurses who did not have any type of training or contact with contents related to Family Nursing. Similar results were found in studies carried out in contexts of primary health care (16) and psychiatric care (17) , which also included lower academic degrees, that is, undergraduate. Higher scores were also found after online training in interacting with families.…”
Section: Discussionsupporting
confidence: 74%
“…(12)(13) Most participating nurses showed a supportive attitude regarding the importance of involving families in nursing care. The same results were found in studies that used the same scale, carried out in different contexts and realities, such as Sweden (14)(15)(16) , Portugal (2,16) and Iceland (17) .…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This may be true for some family members in this study who felt that there is little or no engagement with the nurses when caring for psychiatric patients. Nurses may not collaborate with families when they have inadequate knowledge about family involvement in psychiatric nursing [24]. As such, family members and the nurse may not effectively contribute towards the patients' recovery if they do not collaborate when planning nursing care.…”
Section: Discussionmentioning
confidence: 99%